Padronização de processos e rotinas do núcleo de controle e manutenção do sistema de pagamento - Rizzetti, Daniele Medianeira (2014)
The need for greater administrative efficiency in the public sector makes society increasingly require managers of public institutions who should give priority to the development of its employees skills as well as the utilization of available resources. To make this possible, it is necessary for every individual to know the organizational reality as a whole and not only its function. In this regard, in recent decades, these organizations have made use of some tools in the area of Private Management in pursuit of higher quality and speed in service to the community, making their images respectable to the population. One of the tools that is attracting great interest from managers of public organizations is to standardize processes by mapping them, allowing a greater understanding of how, in fact, products and services are created, clearly showing the problems, the failures and inefficiencies as well as providing benefits, such as reduced process cycle times, decreased costs, improved efficiency and internal efficiency, improving the quality of the work undertaken and increasing the satisfaction of all those people involved. This current study aimed to propose a manual standardization of processes and routines of the Center of Control and Maintenance of the Payment System (NUCOMP) of Coordinator Bureau of Payment Systems (CPAG) of Personnel Management Secretary (PROGEP) at the Federal University of Santa Maria (UFSM) for the dissemination and better understanding in the institution. Therefore, it was performed a research of applied nature, with qualitative and exploratory approach related to its goals, using a study case as its method. Data collection occurred from March to April 2014, and the choice of this sector was due to its importance for UFSM, because it is responsible for managing, feeding and operating the Federal System that generates the payroll of all active and retired employees of this institution. The development of this work brought many contributions to both the academic environment, with reflections and suggestions for future work, but also for the target industry study once it provides a current view of it and can eliminate the unnecessary activities and make a better use of time in activities that, in fact, are relevant. Finally, it can facilitate training and the dissemination of knowledge to new servers that may enter NUCOMP, acting as a practical guide for the knowledge of the reality at this workplace.